Photodynamic therapy in the treatment of onychomycosis – a review - Kalinowska, Katarzyna; Hryncewicz-Gwóźdź, Anita (Dermatology Review/Przegląd Dermatologiczny, 2017)
Toenail onychomycosis is a common infection, affecting up to 14% of the population. Moreover, poor penetration of topical drugs into the nail bed leads to frequent recurrences of the disease. The cure rate of toenail onychomycosis is estimated at 63–76%. An alternative treatment for onychomycosis is photodynamic therapy. Following agents are used in this method: porfimer sodium, rose bengal, methylene blue, 5-aminolevulinic acid and its derivative – methyl ester. The therapy is well tolerated Photodynamic therapy offers an opportunity to achieve a significant cure rate in patients who cannot receive oral therapy. Thanks to systematic improvements in photodynamic therapy, including better photosensitizer penetration into the nail bed and shorter exposure time, photodynamic therapy may be more efficient and cost-effective than other onychomycosis treatments. However, randomized clinical trials evaluating the efficacy of photodynamic therapy of onychomycosis are needed.